Manipulating nanostructure to simultaneously improve the electrical conductivity and strength in microalloyed Al-Zr conductors - S. Y. Jiang (Nature Portfolio, 2018)
Abstract To elude the strength-electrical conductivity trade-off dilemma, a nanostructuring strategy was achieved in microalloyed Al-0.1wt.% Zr conductor by optimizing the processing route, leading to enhanced strength and simultaneously improved electrical conductivity. The nanostructural design involved ultrafine grains with coherent Al3Zr nanoprecipitates dispersed within the grain interior. The key is to create intragranular coherent Al3Zr nanoprecipitates with size of ~6 nm, which not only produce the highest precipitate hardening but also minimize the local strain field to reduce the scattering of electron motion. According to the targeted nanostructures, the processing route was revised to be artificially aged before cold drawing, instead of the post-aging as traditionally employed. The underlying mechanisms for improvement in strength and electrical conductivity were respectively discussed especially in terms of the coherent Al3Zr nanoprecipitates. It was quantitatively revealed from a strengthening model that the intragranular Al3Zr precipitate hardening was the predominant strengthening mechanism. Experimental results from three-dimensional atom probe (3DAP) demonstrating the Zr atom distribution in matrix as well as the geometrical phase analysis (GPA) results of local strain fields around the precipitates provided evidences to rationalize the promotion in electrical conductivity. The nanostructuring strategy in conjunction with the revised processing route offer a general pathway for manufacturing high-performance Al conductors in large-scale industrial applications.